Development and utilization of geothermal energy in China: Current practices and future strategies. (September 2018) - Hou, Jianchao; Cao, Mengchao; Liu, Pingkuo
Abstract: In January 2017, the Chinese government released the first special plan for the development of geothermal energy, named " The 13th five-year plan for geothermal energy development and utilization (2016–2020) ", which promotes the development of geothermal energy to the national energy strategic level. As a stable and low-carbon renewable energy, it is significant to develop geothermal energy to relieve air pollution and supply continuous base load power. This paper first introduces the resource endowments of geothermal energy in China, the current status and development targets of geothermal energy use, as well as series of related policies on China's geothermal energy. Then the economic, environmental and social benefits of geothermal energy development are analyzed respectively. Next, based on the PESTEL framework, this paper analyzes the unfavorable factors in the development of geothermal energy in China. Fourth, based on the PESTEL analysis results, we give some countermeasures and solutions for the future development of China's geothermal energy from two aspects of technology and policy. Finally, based on the above analysis, the corresponding conclusions and policy recommendations are given. Highlights: It is essential for China to develop geothermal energy to meet the needs of energy consumption and relieve air pollution. Resource endowments, development and utilization, development targets and policy tools of China's geothermal energy is discussed. Benefits and obstacles on geothermal energy development and utilization are analyzed. Countermeasures for geothermal utilization are proposed. Policy recommendations are put forward.